ANALISIS STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS ORGANISASI - Hasan Husaini (PT Saha Kreasi Indonesia, 2026)
Human Resource Management (HRM) plays a strategic role in improving organizational productivity. This study aims to analyze HRM strategies in enhancing organizational productivity through recruitment management, training, career development, and performance evaluation systems. The research method used is a qualitative approach through a literature review of relevant scientific sources. The findings indicate that effective HRM strategies can improve employee motivation, competence, and performance, which directly contribute to increased organizational productivity. In addition, the implementation of reward systems, continuous training, and a positive work culture are key supporting factors. However, challenges such as limited budgets, resistance to change, and lack of managerial competence remain obstacles in optimal HRM implementation. In conclusion, well-planned and integrated HRM strategies are essential for sustainably improving organizational productivity.